Características farmacognósticas y rendimiento del aceite esencial de las hojas de Minthostachys mollis “muña” - Orbegozo Paredes, Haidy Maggli (2018)
The present research work was determined the pharmacognostic characteristics and the yield of the essential oil of the leaves of Minthostachys mollis "muña", whose sample was collected from Cochapampa Alta, Santa Cruz de Chuca of district, Santiago de Chuco of province, region La Libertad. Method: The pharmacognostic characteristics of the leaves of Minthostachys mollis "muña" included the determination of macromorphological characteristics; presenting a type of ovate leaf with irregularly serrated edge, with dark green color, with a similar smell to menthol, with a soft texture, size was 1.99 cm ± 0.28 in width, 2.90 cm ± 0.22 in length; Physicochemical parameters were 1.13% ± 0.07 foreign matter, 13.8% ± 0.29 residual moisture, 7.58% ± 0.04 total ash, 0.9% ± 0.02 acid insoluble ash, 4.89% ± 0.05 water-soluble ashes, water-soluble substances, ethanol at 50 ° GL, at 70 ° GL, and at 96 ° GL were 14.06% ± 0.06, 17.06% ± 0.08, 12.62% ± 0.06 and 18.07% ± 0.05 respectively; which agree with permissible ranges in pharmacopoeias; the preliminary phytochemical screening of Miranda and Cuellar, where phytoconstituents such as lactones, triterpenes, reducing sugars, tannins, phenolic compounds, flavonoids and amino acids were identified. The yield of the essential oil was 0.6% ± 0.15 using the clevenger equipment